2020
DOI: 10.1038/s41598-020-68021-2
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide cross-sectional survey on hepatitis B and C screening among workers in Japan

Abstract: In Japan, there is no publicly funded screening for hepatitis B virus (HBV) and hepatitis C virus (HCV) infections (using HBs antigen and HCV antibody, respectively) among workers, and workplace health programmes play a crucial role in reducing viral hepatitis-related deaths. The national number of hepatitis screening tests conducted in the workplace is unknown. To provide baseline data for policy formulation, we conducted a nationwide survey to estimate these parameters using data from approximately 10.5 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
8
0
1
Order By: Relevance
“…However, patients who became aware of their chronic HCV infection through a health checkup were older than those with chronic HBV infection, particularly males. Although the reason for this difference is unclear, Tatemichi et al (25) reported that only 5.23 and 3.82% of Japanese workers had been screened for HBV and HCV infection, respectively, and significantly more workers had been tested for HBV than for HCV infection. The use of hepatitis virus screening tools during health checkups varies between organizations (e.g., official health checkups vs. health checkups for company employees).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients who became aware of their chronic HCV infection through a health checkup were older than those with chronic HBV infection, particularly males. Although the reason for this difference is unclear, Tatemichi et al (25) reported that only 5.23 and 3.82% of Japanese workers had been screened for HBV and HCV infection, respectively, and significantly more workers had been tested for HBV than for HCV infection. The use of hepatitis virus screening tools during health checkups varies between organizations (e.g., official health checkups vs. health checkups for company employees).…”
Section: Discussionmentioning
confidence: 99%
“…The use of hepatitis virus screening tools during health checkups varies between organizations (e.g., official health checkups vs. health checkups for company employees). HBV infection is recognized as an occupational exposure risk for health care workers and laboratory technicians (25), which may be attributed to the original Japanese Union Health Insurance system in which beneficiaries underwent comprehensive health examinations as part of a mandatory health checkup; these examinations included screening for HBV, but not HCV (25). In female patients, the age when they became aware of their chronic hepatitis virus infection was high, even though it was HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to screen all adult residents in the town of Nagawa (approximately 4500). Since the HCV-positive rate is reportedly 0.35% among workers in Japan [ 14 ], it is estimated that approximately 16 people are HCVAb-positive.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated institutions that conducted health screenings in the FY 2016 and reported examination rates of 7.8% and 4.9% for HBsAg and anti-HCV, respectively, in the health insurance association for hepatitis virus testing during workplace checkups in the UHI (11). In this survey, there were many people who are examined every year in same Health Administration Center, and it was revealed that about 70% of the respondents underwent hepatitis screening every year over three years, regardless of whether the test was negative or positive.…”
Section: Current Status and Issues Of Viral Hepatitis In The Workplacementioning
confidence: 99%